EFFORTS TO IMPROVE TABLE TENNIS PROFICIENCY OF HIGH SCHOOL STUDENTS THROUGH THE USE OF INTERVAL TRAINING METHODS - Sarjono Sarjono; Budi Setiawan (Prodi Teknologi Pendidikan, 2023)
The purpose of this classroom action research was to improve table tennis candy skills through the use of the interval training method in students of class XI IPA 4 semester 2 SMA Negeri 3 Sukoharjo in the academic year 2021/ 2022. This research is a type of classroom action research, with research subjects being students of class XI IPA 4 semester 2 SMA Negeri 3 Sukoharjo in the academic year 2014/2015. The source of the data came from observations of table tennis training activities through the interval training method. Data collection techniques used observation methods, test formats, questionnaires and point documentation. Data analysis techniques used cycle points consisting of two cycles with steps including planning, evaluation and reflection. Performance indicators include the results of the table tennis skill test using the backboard test and students' interest or motivation in participating in the training program using the interval method. The results showed that the interval training method in the game of table tennis carried out by the researcher showed the results of cycle 1: students' skills were in the moderate category 11 students, 14 students were lacking and 7 students were not very low. Cycle 2 results: showed student skills in the security guard category 13 students, category good 11 students and very good category 8 students. Getting to the point of increasing students' skills in playing table tennis based on class XI IPA 4 semester 2 SMA Negeri 3 Sukorejo in the 2021/ 2022. academic year, this is evident from the results of research conducted in two cycles, namely the results of hitting students right on target that have been determined have increased from the test results cycle I with the results of the test cycle II.